Efficient spraying soldering paste and preparation method thereof

By using lead-free solder powder and formula flux with particle size of 15 to 25 μm, an efficient spray solder paste is formed, which solves the problems of high cost and poor wettability of the existing solder paste, and achieves efficient spray arrangement and stable solder joint quality. Improves the reliability and production efficiency of electronic products.

CN119407397AActive Publication Date: 2025-02-11DONGGUAN YONGAN TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411642157.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing solder paste is costly and can only be used for steel screen printing, and the wettability is poor during the printing process, which affects the reliability and production efficiency of electronic products.

Method used

Lead-free solder powder with particle sizes of 15 to 25 μm and formula flux are used to fully mix it through a vacuum mixer to form an efficient jet solder paste, and various jetting devices can be used for jet arrangement.

Benefits of technology

The cost of solder paste is reduced, the layout efficiency of solder paste is improved, the wettability is improved, and the stability of solder joint quality is ensured, thereby improving the reliability and production efficiency of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138752990000021
    Figure BDA0005138752990000021
  • Figure BDA0005138752990000051
    Figure BDA0005138752990000051
  • Figure BDA0005138752990000071
    Figure BDA0005138752990000071
Patent Text Reader

Abstract

The invention discloses high-efficiency spraying soldering paste and a preparation method thereof. The high-efficiency spraying soldering paste is composed of the following raw materials in percentage by mass: 75-85% of lead-free soldering powder; the particle size of the lead-free solder powder is 15-25 [mu] m; 15%-25% of soldering flux; the soldering flux is composed of the following raw materials in parts by weight: 15-25 parts of polymerized rosin; 5-15 parts of hydrogenated rosin; 5-10 parts of rosin glyceride; 3 to 5 parts of ethyl palmitate; and 3-5 parts of calcium chloride and the like. The lead-free solder powder with the particle size of 15-25 microns is adopted, the cost is low, and the soldering flux of the formula is used in a matched mode, so that the product can be subjected to injection arrangement through various injection devices, a traditional steel mesh printing mode is replaced, the arrangement efficiency of the solder paste is effectively improved, and the production cost is reduced. In addition, the soldering paste is very good in wettability in the spraying process, spraying is smooth, the welding spot quality is stable, and the reliability and the production efficiency of electronic products can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solder paste technology, in particular to a highly efficient jet solder paste and a preparation method thereof. Background Art

[0002] Solder paste is also called solder paste, and its English name is solder paste, gray paste. Solder paste is a new type of welding material that came into being with SMT. It is a paste mixture formed by mixing solder powder, flux and other surfactants, thixotropic agents, etc. It is mainly used for welding electronic components such as PCB surface resistors, capacitors, ICs, etc. in the SMT industry. With the development of electronic products, electronic products are getting smaller and smaller, and the pads are getting smaller and smaller. With the change of market technology, the existing solder paste can no longer meet market requirements. By using tiny tin powder to produce halogen-free solder paste, it plays a major role in the electronic welding of micro solder joints. When applied to different industries and products, it can achieve high-tech, high-requirement, micro solder joint welding, so it is widely used in military industry, mobile phones, chips, medical treatment, watches, other micro solder joint welding and other fields.

[0003] The particle size of the solder powder used in the current solder paste is generally less than 10μm, which is very small and has a high cost. In addition, the solder paste formed by mixing the solder powder with the flux can usually only be arranged by steel screen printing, which is inefficient. In addition, the solder paste has problems such as poor wettability, unsmooth printing, and unstable solder joint quality during the printing process, which affects the reliability and production efficiency of electronic products. Therefore, it is necessary to study a solution to solve the above problems. Summary of the invention

[0004] In view of this, the present invention aims at the deficiencies of the prior art, and its main purpose is to provide a high-efficiency jet solder paste and a preparation method thereof, which can effectively solve the problems of the existing solder paste having high cost, only being able to be printed by steel screen and having poor wettability during printing.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A highly efficient jet solder paste, comprising the following raw materials in percentage by weight:

[0007] Lead-free solder powder 75%~85%;

[0008] The particle size of the lead-free solder powder is 15 to 25 μm;

[0009] Flux 15%~25%;

[0010] The soldering flux is composed of the following raw materials in parts by weight:

[0011]

[0012] As a preferred solution, the lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and tin is the balance.

[0013] As a preferred embodiment, the method for preparing the lead-free solder powder comprises the following steps:

[0014] Step 1: Preparation of molten alloy:

[0015] (1) selecting an appropriate amount of tin raw material, and adding bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively;

[0016] (2) raising the temperature of the melting furnace to 250-360° C. and maintaining the melting time at 3.5-4.5 hours to obtain a mixed liquid a;

[0017] Step 2: Polymerization reaction:

[0018] (1) putting the prepared mixed liquid a into a reaction kettle;

[0019] (2) Heating in a nitrogen or vacuum atmosphere with a nitrogen injection rate of 1.8 l / min;

[0020] (3) adding organic antimony as a stabilizer, stirring and heating to 500-600° C., and performing a polymerization reaction to obtain a mixed liquid b;

[0021] Step 3: Cooling and filtration:

[0022] (1) Cooling the mixed liquid b naturally for 24 to 28 hours;

[0023] (2) filtering the mixed liquid b to obtain a filtrate;

[0024] Step 4: Grinding: The filtered material is placed in a grinding device for grinding to a particle size of 15 to 25 μm;

[0025] Step 5: Drying:

[0026] (1) putting the ground filtrate into a drying oven for drying;

[0027] (2) The temperature of the drying oven is raised to 120-150° C. and the drying time is 2-3 hours to obtain lead-free solder powder.

[0028] As a preferred embodiment, the polymerized rosin is RJH-145 polymerized rosin.

[0029] As a preferred embodiment, the hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0030] A method for preparing an efficient spray solder paste comprises the following steps:

[0031] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion;

[0032] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 150°C to 170°C, stir until completely melted, cool to obtain a paste-like flux, and store in a cold storage at 0 to 10°C for later use;

[0033] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 15 to 20 minutes, then fill with nitrogen and stir at medium speed for 50 to 60 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 10 to 15 minutes to obtain solder paste.

[0034] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0035] By adopting lead-free solder powder with a particle size of 15 to 25 μm, which has low cost, and using the flux with the formula of the present invention in combination, the product can be sprayed and arranged using various spray devices, replacing the traditional steel screen printing method, effectively improving the arrangement efficiency of the solder paste, and the solder paste of the present invention has very good wettability during the spraying process, smooth spraying, and stable solder joint quality, which is beneficial to improving the reliability and production efficiency of electronic products. DETAILED DESCRIPTION

[0036] The present invention discloses a highly efficient spray solder paste, which is composed of the following raw materials in percentage by mass:

[0037] Lead-free solder powder 75%~85%;

[0038] The particle size of the lead-free solder powder is 15 to 25 μm;

[0039] Flux 15%~25%;

[0040] The soldering flux is composed of the following raw materials in parts by weight:

[0041]

[0042] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0043] The preparation method of the lead-free solder powder comprises the following steps:

[0044] Step 1: Preparation of molten alloy:

[0045] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0046] (2) The melting furnace is heated to 250-360° C. and the melting time is maintained at 3.5-4.5 hours to obtain a mixed liquid a.

[0047] Step 2: Polymerization reaction:

[0048] (1) The prepared mixed liquid a is put into a reaction kettle.

[0049] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0050] (3) adding organic antimony as a stabilizer, stirring and heating to 500-600° C., and performing polymerization reaction to obtain a mixed liquid b.

[0051] Step 3: Cooling and filtration:

[0052] (1) Allow the mixed liquid b to cool naturally for 24 to 28 hours.

[0053] (2) Filter the mixed liquid b to obtain a filtrate.

[0054] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 15 to 25 μm.

[0055] Step 5: Drying:

[0056] (1) The ground filtrate is placed in a drying oven for drying.

[0057] (2) The temperature of the drying oven is raised to 120-150° C. and the drying time is 2-3 hours to obtain lead-free solder powder.

[0058] The present invention also discloses a method for preparing the aforementioned high-efficiency spray solder paste, comprising the following steps:

[0059] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0060] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 150°C to 170°C, stir until completely melted, cool to obtain a paste-like flux, and store in a cold storage at 0 to 10°C for later use.

[0061] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 15 to 20 minutes, then fill with nitrogen and stir at medium speed for 50 to 60 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 10 to 15 minutes to obtain solder paste.

[0062] The present invention is further described in detail with multiple embodiments below:

[0063] Embodiment 1:

[0064] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0065] Lead-free solder powder 80%;

[0066] The particle size of the lead-free solder powder is 20 μm;

[0067] Flux 20%;

[0068] The soldering flux is composed of the following raw materials in parts by weight:

[0069]

[0070]

[0071] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 18%, the copper content is 0.8%, the silver content is 2%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0072] The preparation method of the lead-free solder powder comprises the following steps:

[0073] Step 1: Preparation of molten alloy:

[0074] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0075] (2) The temperature of the melting furnace was raised to 300° C. and the melting time was maintained at 3.5 hours to obtain a mixed liquid a.

[0076] Step 2: Polymerization reaction:

[0077] (1) The prepared mixed liquid a is put into a reaction kettle.

[0078] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0079] (3) adding organic antimony as a stabilizer, stirring and heating to 550° C., and performing polymerization reaction to obtain a mixed liquid b.

[0080] Step 3: Cooling and filtration:

[0081] (1) The mixed liquid b was naturally cooled for 25 hours.

[0082] (2) Filter the mixed liquid b to obtain a filtrate.

[0083] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 20 μm.

[0084] Step 5: Drying:

[0085] (1) The ground filtrate is placed in a drying oven for drying.

[0086] (2) The drying oven is heated to 130° C. and the drying time is 2.3 hours to obtain lead-free solder powder.

[0087] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0088] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0089] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 160°C, stir until completely melted, cool to obtain a paste flux, and store in a cold storage at 8°C for later use.

[0090] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 17 minutes, then fill with nitrogen and stir at medium speed for 55 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 12 minutes to obtain solder paste.

[0091] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and its wetting time after spraying is 0.91s, and the wetting force is enhanced.

[0092] Embodiment 2:

[0093] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0094] Lead-free solder powder 75%;

[0095] The particle size of the lead-free solder powder is 15 μm;

[0096] Flux 25%;

[0097] The soldering flux is composed of the following raw materials in parts by weight:

[0098]

[0099]

[0100] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 20%, the copper content is 0.5%, the silver content is 0.8%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0101] The preparation method of the lead-free solder powder comprises the following steps:

[0102] Step 1: Preparation of molten alloy:

[0103] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0104] (2) The temperature of the melting furnace was raised to 250° C. and the melting time was maintained at 4 hours to obtain a mixed liquid a.

[0105] Step 2: Polymerization reaction:

[0106] (1) The prepared mixed liquid a is put into a reaction kettle.

[0107] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0108] (3) adding organic antimony as a stabilizer, stirring and heating to 500° C. to perform polymerization reaction to obtain a mixed liquid b.

[0109] Step 3: Cooling and filtration:

[0110] (1) The mixed liquid b was naturally cooled for 26 hours.

[0111] (2) Filter the mixed liquid b to obtain a filtrate.

[0112] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 15 μm.

[0113] Step 5: Drying:

[0114] (1) The ground filtrate is placed in a drying oven for drying.

[0115] (2) The drying oven is heated to 120° C. and the drying time is 2 hours to obtain lead-free solder powder.

[0116] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0117] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0118] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 150°C, stir until completely melted, cool to obtain a paste-like flux, and store in a 0°C cold storage for later use.

[0119] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 15 minutes, then fill with nitrogen and stir at medium speed for 50 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 14 minutes to obtain solder paste.

[0120] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and its wetting time after spraying is 0.88s, and the wetting force is enhanced.

[0121] Embodiment 3:

[0122] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0123] Lead-free solder powder 77%;

[0124] The particle size of the lead-free solder powder is 22 μm;

[0125] Flux 23%;

[0126] The soldering flux is composed of the following raw materials in parts by weight:

[0127]

[0128] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 25%, the copper content is 1.1%, the silver content is 3%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0129] The preparation method of the lead-free solder powder comprises the following steps:

[0130] Step 1: Preparation of molten alloy:

[0131] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0132] (2) The temperature of the melting furnace was raised to 360° C. and the melting time was maintained at 3.8 hours to obtain a mixed liquid a.

[0133] Step 2: Polymerization reaction:

[0134] (1) The prepared mixed liquid a is put into a reaction kettle.

[0135] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0136] (3) adding organic antimony as a stabilizer, stirring and heating to 600° C., and performing polymerization reaction to obtain a mixed liquid b.

[0137] Step 3: Cooling and filtration:

[0138] (1) The mixed liquid b is cooled naturally for 24 hours.

[0139] (2) Filter the mixed liquid b to obtain a filtrate.

[0140] Step 4: Grinding: The filtered material is placed in a grinding device for grinding to a particle size of 22 μm.

[0141] Step 5: Drying:

[0142] (1) The ground filtrate is placed in a drying oven for drying.

[0143] (2) The temperature of the drying oven is raised to 150° C. and the drying time is 2.5 hours to obtain lead-free solder powder.

[0144] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0145] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0146] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 170°C, stir until completely melted, cool to obtain a paste-like flux, and store in a cold storage at 10°C for later use.

[0147] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 20 minutes, then fill with nitrogen and stir at medium speed for 60 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 13 minutes to obtain solder paste.

[0148] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and its wetting time after spraying is 0.80s, and the wetting force is enhanced.

[0149] Embodiment 4:

[0150] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0151] Lead-free solder powder 84%;

[0152] The particle size of the lead-free solder powder is 25 μm;

[0153] Flux 16%;

[0154] The soldering flux is composed of the following raw materials in parts by weight:

[0155]

[0156]

[0157] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 23%, the copper content is 1%, the silver content is 4.5%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0158] The preparation method of the lead-free solder powder comprises the following steps:

[0159] Step 1: Preparation of molten alloy:

[0160] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0161] (2) The temperature of the melting furnace was raised to 320° C. and the melting time was maintained at 4.2 hours to obtain a mixed liquid a.

[0162] Step 2: Polymerization reaction:

[0163] (1) The prepared mixed liquid a is put into a reaction kettle.

[0164] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0165] (3) adding organic antimony as a stabilizer, stirring and heating to 520° C. to perform polymerization reaction to obtain a mixed liquid b.

[0166] Step 3: Cooling and filtration:

[0167] (1) The mixed liquid b is naturally cooled for 28 hours.

[0168] (2) Filter the mixed liquid b to obtain a filtrate.

[0169] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 25 μm.

[0170] Step 5: Drying:

[0171] (1) The ground filtrate is placed in a drying oven for drying.

[0172] (2) The drying oven is heated to 125° C. and the drying time is 3 hours to obtain lead-free solder powder.

[0173] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0174] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0175] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 155°C, stir until completely melted, cool to obtain a paste flux, and store in a 5°C cold storage for later use.

[0176] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 18 minutes, then fill with nitrogen and stir at medium speed for 53 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 15 minutes to obtain solder paste.

[0177] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and its wetting time after spraying is 0.89s, and the wetting force is enhanced.

[0178] Embodiment 5:

[0179] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0180] Lead-free solder powder 85%;

[0181] The particle size of the lead-free solder powder is 24 μm;

[0182] Flux 15%;

[0183] The soldering flux is composed of the following raw materials in parts by weight:

[0184]

[0185]

[0186] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 22%, the copper content is 1.2%, the silver content is 4%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0187] The preparation method of the lead-free solder powder comprises the following steps:

[0188] Step 1: Preparation of molten alloy:

[0189] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0190] (2) The melting furnace was heated to 350° C. and the melting time was maintained at 4.5 hours to obtain a mixed liquid a.

[0191] Step 2: Polymerization reaction:

[0192] (1) The prepared mixed liquid a is put into a reaction kettle.

[0193] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0194] (3) adding organic antimony as a stabilizer, stirring and heating to 580° C. to perform polymerization reaction to obtain a mixed liquid b.

[0195] Step 3: Cooling and filtration:

[0196] (1) The mixed liquid b was naturally cooled for 27 hours.

[0197] (2) Filter the mixed liquid b to obtain a filtrate.

[0198] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 24 μm.

[0199] Step 5: Drying:

[0200] (1) The ground filtrate is placed in a drying oven for drying.

[0201] (2) The drying oven is heated to 135° C. and the drying time is 2.1 hours to obtain lead-free solder powder.

[0202] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0203] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0204] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 165°C, stir until completely melted, cool to obtain a paste flux, and store in a 7°C cold storage for later use.

[0205] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 19 minutes, then fill with nitrogen and stir at medium speed for 58 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 10 minutes to obtain solder paste.

[0206] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and its wetting time after spraying is 0.84, and the wetting force is enhanced.

[0207] Embodiment 6:

[0208] This embodiment discloses a highly efficient jet solder paste, which is composed of the following raw materials in percentage by weight:

[0209] Lead-free solder powder 76%;

[0210] The particle size of the lead-free solder powder is 18 μm;

[0211] Flux 24%;

[0212] The soldering flux is composed of the following raw materials in parts by weight:

[0213]

[0214] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15%, the copper content is 0.9%, the silver content is 3.5%, and the tin content is the balance. The polymerized rosin is RJH-145 polymerized rosin. The hydrogenated rosin is AX-80 fully hydrogenated rosin.

[0215] The preparation method of the lead-free solder powder comprises the following steps:

[0216] Step 1: Preparation of molten alloy:

[0217] (1) Select an appropriate amount of tin raw material and add bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively.

[0218] (2) The temperature of the melting furnace was raised to 330° C. and the melting time was maintained at 4.3 hours to obtain a mixed liquid a.

[0219] Step 2: Polymerization reaction:

[0220] (1) The prepared mixed liquid a is put into a reaction kettle.

[0221] (2) The temperature is raised in a nitrogen or vacuum atmosphere, with the nitrogen injection rate being 1.8 l / min.

[0222] (3) adding organic antimony as a stabilizer, stirring and heating to 560° C. to perform polymerization reaction to obtain a mixed liquid b.

[0223] Step 3: Cooling and filtration:

[0224] (1) The mixed liquid b was naturally cooled for 25 hours.

[0225] (2) Filter the mixed liquid b to obtain a filtrate.

[0226] Step 4: Grinding: Place the filtered material into a grinding device for grinding to a particle size of 18 μm.

[0227] Step 5: Drying:

[0228] (1) The ground filtrate is placed in a drying oven for drying.

[0229] (2) The drying oven is heated to 140° C. and the drying time is 2.8 hours to obtain lead-free solder powder.

[0230] This embodiment also discloses a method for preparing the aforementioned efficient spray solder paste, comprising the following steps:

[0231] (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion.

[0232] (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 158°C, stir until completely melted, cool to obtain a paste flux, and store in a 6°C cold storage for later use.

[0233] (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 16 minutes, then fill with nitrogen and stir at medium speed for 52 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 11 minutes to obtain solder paste.

[0234] After testing, it was found that the highly efficient spray solder paste prepared by the formula and method of this embodiment can be sprayed by various spray devices, and the wetting time after spraying is 0.85s, and the wetting force is enhanced.

[0235] The design focus of the present invention is that by adopting lead-free solder powder with a particle size of 15 to 25 μm, which has low cost, and using the flux of the present invention in combination, the product can be sprayed and arranged using various spray devices, replacing the traditional steel screen printing method, effectively improving the arrangement efficiency of the solder paste, and the solder paste of the present invention has very good wettability during the spraying process, smooth spraying, and stable solder joint quality, which is beneficial to improving the reliability and production efficiency of electronic products.

[0236] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A highly efficient spray solder paste, characterized by: It is composed of the following raw materials in percentage by weight: Lead-free solder powder 75%~85%; The particle size of the lead-free solder powder is 15 to 25 μm; Flux 15%~25%; The soldering flux is composed of the following raw materials in parts by weight:

2. The high-efficiency spray solder paste according to claim 1, characterized in that: The lead-free solder powder is composed of four elements of tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and tin is the balance.

3. The high-efficiency spray solder paste according to claim 1 or 2, characterized in that: The preparation method of the lead-free solder powder comprises the following steps: Step 1: Preparation of molten alloy: (1) selecting an appropriate amount of tin raw material, and adding bismuth-tin alloy, silver-tin alloy, and copper-tin alloy into a melting furnace respectively; (2) raising the temperature of the melting furnace to 250-360° C. and maintaining the melting time at 3.5-4.5 hours to obtain a mixed liquid a; Step 2: Polymerization reaction: (1) putting the prepared mixed liquid a into a reaction kettle; (2) Heating in a nitrogen or vacuum atmosphere with a nitrogen injection rate of 1.8 l / min; (3) adding organic antimony as a stabilizer, stirring and heating to 500-600° C., and performing a polymerization reaction to obtain a mixed liquid b; Step 3: Cooling and filtration: (1) Cooling the mixed liquid b naturally for 24 to 28 hours; (2) filtering the mixed liquid b to obtain a filtrate; Step 4: Grinding: The filtered material is placed in a grinding device for grinding to a particle size of 15 to 25 μm; Step 5: Drying: (1) putting the ground filtrate into a drying oven for drying; (2) The temperature of the drying oven is raised to 120-150° C. and the drying time is 2-3 hours to obtain lead-free solder powder.

4. The high-efficiency spray solder paste according to claim 1, characterized in that: The polymerized rosin is RJH-145 polymerized rosin.

5. The high-efficiency spray solder paste according to claim 1, characterized in that: The hydrogenated rosin is AX-80 fully hydrogenated rosin.

6. A method for preparing a highly efficient jet solder paste as claimed in any one of claims 1 to 5, characterized in that: The following steps are included: (1) Weigh polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bisstearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid according to proportion; (2) Add polymerized rosin, hydrogenated rosin, rosin glycerol ester, ethyl palmitate, calcium chloride, ethylene bis-12-hydroxystearic acid amide, ethylene bis-stearamide, oxidized polyethylene wax, 12-hydroxystearic acid, diethylene glycol butyl ether, triethylene glycol dibutyl ether, hexylene glycol, suberic acid and sebacic acid into the same container, heat to 150°C to 170°C, stir until completely melted, cool to obtain a paste-like flux, and store in a cold storage at 0 to 10°C for later use; (3) Weigh lead-free solder powder and flux in proportion, pour into a vacuum mixer, stir at low speed for 15 to 20 minutes, then fill with nitrogen and stir at medium speed for 50 to 60 minutes to fully mix the lead-free solder powder and flux, then evacuate and stir at medium speed for 10 to 15 minutes to obtain solder paste.

Citation Information

Patent Citations

  • Lead-free solder paste for needle cylinder and preparation method

    CN102528328A

  • Lead-free soldering paste capable of improving welding quality and preparation method thereof

    CN108057965A

  • Novel lead-free tin paste and preparation method thereof

    CN109848603A

  • Soldering flux

    JP1999254184A

  • Flux for lead-free solder, and lead-free solder paste

    JP2015006687A